Guided‐modified coronally advanced flap: Novel digital approach to treat multiple gingival recessions. Workflow and case study - Santamaria, Mauro Pedrine; Bonafé, Ana Carolina Ferreira [UNESP]; Rossato, Amanda [UNESP]; Miguel, Manuela Maria Viana; da Costa, Andrews Porto; Mathias‐Santamaria, Ingrid Fernandes; Nunes, Marcelo Pereira; Queiroz, Lucas Araújo (Wiley, 2025)
BACKGROUND: Gingival recession (GR) poses esthetic and functional challenges for patients, particularly in cases of multiple adjacent defects. Traditional surgical approaches, such as the modified coronally advanced flap (MCAF) with connective tissue grafts (CTG), demand high levels of precision and skill, making outcomes reliant on clinician expertize. The integration of digital technologies, including cone-beam computed tomography (CBCT) and computer-aided design and manufacturing (CAD-CAM), offers a novel, standardized approach to enhance procedural accuracy and predictability. METHODS: This case study describes the use of the guided-modified coronally advanced flap (g-MCAF) for the treatment of multiple GR defects. A patient whose main concern was the esthetic appearance of her teeth was treated. Using an intraoral scanner, CBCT data, and CAD-CAM software, surgical guides were designed and 3D printed using a dedicated resin, assuring precise adaptation to the patients' teeth. The guides delineated MCAF oblique incisions and free gingival graft dimensions tailored to fit into the area, facilitating flap design, and graft harvesting. RESULTS: The guided MCAF (g-MCAF) procedure successfully achieved complete root coverage. At the 6-month follow-up, recession reduction was observed, measuring 2.22 mm for tooth #5, 2.59 mm for tooth #6, and 2.26 mm for tooth #7. Gingival thickness also increased, reaching 1.23, 1.16, and 1.45 mm, respectively. Additionally, the patient reported improved esthetics and reduced hypersensitivity. CONCLUSION: The g-MCAF technique may have the potential to serve as a reliable aid to execute MCAF in the management of multiple GR defects. KEY POINTS: A guided surgical approach (g-MCAF) using digital technologies allows for precise flap design and graft harvesting, which may help control variability and minimize errors during root coverage procedures. The integration of CBCT, intraoral scanning, and CAD-CAM technologies supports preoperative planning, potentially contributing to safer and more predictable outcomes, particularly in cases requiring connective tissue grafts. This innovative approach may assist in simplifying complex surgical techniques, improving clinician confidence, and serving as both a clinical and an educational tool for periodontal plastic surgery.